2008
DOI: 10.1002/pon.1378
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and dietary change after diagnosis and cancer‐related symptoms in long‐term survivors of breast cancer: CALGB 79804

Abstract: Objective Improving diet and exercise can reduce survivors' risk of cancer-related fatigue, poor physical functioning, and potentially recurrence. A cancer diagnosis can represent a “teachable moment,” leading survivors to make positive changes in diet and exercise behaviors; however, little is known about how often this occurs or about factors that enhance or limit survivors' ability to make these changes. This cross-sectional descriptive study investigated both the prevalence and clustering of self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 17 publications
7
97
0
3
Order By: Relevance
“…Shaharudin et al (2013) also reported that breast cancer survivors in Malaysia changed their dietary habits after breast cancer diagnosis and the main dietary changes made were reduced intake of high fat foods and increased intake of fruits and vegetables. Similar to other studies in western countries (Thomson et al, 2002;Patterson et al, 2003;Alfano et al, 2009), we found that the common dietary changes reported by the respondents in this study included decreased consumption of high fat foods, added fat foods, red meat, pork, poultry and high sugar foods and increased consumption of fish, fruits, vegetables and whole grains. Dairy products such as low fat milk and reduced fat cheese were highly avoided by many of the women.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Shaharudin et al (2013) also reported that breast cancer survivors in Malaysia changed their dietary habits after breast cancer diagnosis and the main dietary changes made were reduced intake of high fat foods and increased intake of fruits and vegetables. Similar to other studies in western countries (Thomson et al, 2002;Patterson et al, 2003;Alfano et al, 2009), we found that the common dietary changes reported by the respondents in this study included decreased consumption of high fat foods, added fat foods, red meat, pork, poultry and high sugar foods and increased consumption of fish, fruits, vegetables and whole grains. Dairy products such as low fat milk and reduced fat cheese were highly avoided by many of the women.…”
Section: Discussionsupporting
confidence: 78%
“…In a study of prostate, colon and breast cancer survivors, 45% had increased fruit and vegetable intakes but lower precentage (28.5%) reported lower intake of fat (Patterson et al, 2003). Alfano et al (2009) showed that 44% of breast cancer survivors decreased fat intake, 42% increased fiber intake, and 43% increased consumption of fruits and vegetables. These studies supported that breast cancer patients were more likely to make healthful dietary changes following a breast cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also found that self-efficacy is an important predictor of exercise behavior among cancer survivors (Haas, 2000;Lev, 1997), and exercise interventions that incorporate self-efficacy strategies have been particularly effective (Bennett, Lyons, Winters-Stone, Nail, & Scherer, 2007). The key role of social support observed here is consistent with other reports about the relationship between health promotion and social support in those with cancer and other chronic health conditions (Alfano et al, 2009;Rimmer & Braddock, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…Even survivors who were not exercising before diagnosis may experience declines in their overall levels of household or occupational activities. In some studies, survivors who are farther from diagnosis have reported increases in physical activity in response to a cancer diagnosis (19)(20)(21). National surveys in the United States have shown that the percentage of cancer survivors who meet recommendations for aerobic exercise varies depending on cancer site, ranging from 21% to 43%; among those with no history of cancer, 36.6% were meeting recommendations.…”
Section: Exercisementioning
confidence: 99%